The girl with the lower back tattoo - Schumer, Amy (Gallery Books, 2016)
Amy Schumer, Emmy Award-winning comedian, actress, writer, and star, mines her past for stories about her teenage years, her family, relationship, and sex, and shares the experiences that have shaped who she is--a woman with the courage to bare her soul and stand up for what she believes in, all while making us laugh. Ranging from the raucous to the romantic, the heartfelt to the harrowing, this highly entertaining and universally appealing collection is the literary equivalent of a night out with your best friend -- an unforgettable and fun adventure you wish could last forever. --